Alendronate treatment induces IL-1B expression and apoptosis in glioblastoma cell line. - Tricarico, Paola Maura; Epate, Angeladine; Celsi, Fulvio; Crovella, Sergio (Inflammopharmacology, 2018)
Alendronate (ALD), one among the nitrogen-containing bisphosphonates (NBPs), is currently used for the treatment of many pathological conditions. Unfortunately, although generally tolerated, NBPs treatment has been associated with central nervous system (CNS) adverse outcomes, such as amnesia, hallucinations and visual disturbances. So, we analyzed the effect of ALD treatment in glial cells, the main sources of cholesterol for neurons and principal cells involved in the immunological defense of the brain. We treated a glial cell line (U87-MG) with increasing doses of ALD (0.1, 1, 10, 25, 50 μM) for 48 h, aimed at evaluating the influence of this drug treatment on IL-1B expression, NLRP3 and CASP1 expression, mitochondrial activity and apoptotic cell death. We observed that ALD treatment, at the higher concentrations, induced a significant increase of IL-1B, NLRP3, CASP1 expression, provoked apoptosis and also mitochondrial damage in U87-MG. Considering the reported CNS adverse outcomes of NBPs treatment, our results confirm ALD side-effects on glial cell model.
Keywords: Alendronate; Apoptosis; Brain; Cell Line, Tumor; Diphosphonates; Glioblastoma; Humans; Interleukin-1beta; Neuroglia